Study on Software Quality Improvement based on Rayleigh Model and PDCA Model - Ning Jingfeng; Hu Ming (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
As the software industry gradually becomes mature, software quality is regarded as the life of a software enterprise. This article discusses how to improve the quality of software, applies Rayleigh model and PDCA model to the software quality management, combines with the defect removal effectiveness index, exerts PDCA model to solve the problem of quality management objectives when using the Rayleigh model in bidirectional quality improvement strategies of software quality management, and puts it into the application to achieve good results. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3086